The Aerial Firefighting Vehicle Routing Problem - Chalabi, W.A.A.; Bombelli, A.; Purdam, G. (Nanyang Technological University, 2024)
Optimizing the routes of firefighting aircraft can lead to a better containment of wildfires, hence yielding great environmental and societal value. In this paper, a novel formulation of the Vehicle Routing Problem (VRP) is developed that is a capacitated multi-trip VRP with time-windows and hierarchical objectives. The primary objective is to minimize the time of carrying out all requested drops, and the secondary objective is to minimize the total flight time. Two types of aircraft are used: scoopers and tankers. The main difference is that scoopers can refill their water tank from a water body. By adjusting the capacity and speed of the aircraft, most firefighting aircraft can be modeled using these two types, including helicopters. The user can input the number and types of aircraft available, the locations of airfield, fires, and nearest water body, intensity of each fire, and more. Several random cases and case studies based on real wildfires were solved within the expert-recommended time limit of 5 minutes, yielding reasonable optimized routes. The problem is scalable and sizes ranging from one to 80 water drops were tested and solved within 22 minutes. Furthermore, given a certain wildfire event, the model can be simulated with various aircraft combinations to gain insights into fleet optimization. In one case study, it was demonstrated that replacing a scooper with a tanker can result in halving the total operation time. Strategic fleet planning is also demonstrated in a case study with the use of Monte Carlo simulation, in order to compare the performance of different fleet options for a given setting. Therefore, the model is not only applicable in live situations, but can also be used as a supportive tool in planning for upcoming fire seasons, or reviewing and learning from past fires.